Can HIV/AIDS be fought by targeting youths in Zambia? Analysis of the Knowledge, Attitudes and Sexual Behaviour among youths aged 15 – 24 years. - Bupe Bwalya Bwalya; Andrew Banda; Stanley Jere; Patrick Amanzi; Peter Funsani (Epidemiology, Biostatistics and Public Health)
Background: Although people of any age are susceptible to HIV, youths aged 15 – 24 face disproportionate risk of contracting it because of challenges that they face with regard to correct HIV and AIDS related knowledge, attitudes and practices. This study was aimed at determining whether HIV and AIDS can be fought by targeting interventions at youths aged 15 – 24 years by assessing their current knowledge, attitudes and sexual behaviours in Zambia.  Methods: The study utilised secondary data from a self-weighting nationally representative sample of the 2009 Zambia Sexual Behaviour Survey. Results: Generally correct comprehensive knowledge is very low among youths (43 percent). This is in spite having good command of general and full general knowledge and the ABCs of HIV and AIDS prevention. Attitudes towards PLHIV, Condom use and HIV counselling and testing were negative. About one third (58 percent) of youths in Zambia have a history of early sexual debut (sex before age 15) with more females (64 percent) than males (51 percent) having hard sex. Male youths were more likely to have used a condom with most recent sexual partner as compared to females (AOR=0.265, 95%CI: 0.160, 0.438; p<0.001). Youths in rural areas had reduced odds of using a condom during their first sexual intercourse compared with those in urban areas (AOR=0.530, 95%CI: 0.387, 0.726; p<0.001). Conclusions: Therefore, it can be seen lack of comprehensive correct knowledge, gender disparities, poor educational levels, youth’s age and place of residence are some of the contributing factors that may hinder the fight against HIV/AIDS among youths in Zambia. Key words: Youths; HIV/AIDS; Knowledge; Attitudes; Behaviour, Zambia